2022
DOI: 10.3390/plants11212983
|View full text |Cite
|
Sign up to set email alerts
|

Time Course RNA-seq Reveals Soybean Responses against Root-Lesion Nematode and Resistance Players

Abstract: Pratylenchus brachyurus causes serious damage to soybean production and other crops worldwide. Plant molecular responses to RLN infection remain largely unknown and no resistance genes have been identified in soybean. In this study, we analyzed molecular responses to RLN infection in moderately resistant BRSGO (Chapadões—BRS) and susceptible TMG115 RR (TMG) Glycine max genotypes. Differential expression analysis revealed two stages of response to RLN infection and a set of differentially expressed genes (DEGs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…These may be related to agronomic traits resulting from the domestication process (Tables S6, S7). For example, Glyma.17G128200 and Glyma.10G295400 are associated with soybean seed yield traits [ 27 , 28 ], Glyma.15G130000 is associated with soybean seed protein concentration [ 29 ], Glyma.11G092100 was demonstrated to directly influence the anabolism of sucrose in soybean [ 30 ], and Glyma.12G143200 and Glyma.13G285300 are associated with soybean cyst nematode and root-lesion nematode resistance, respectively [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…These may be related to agronomic traits resulting from the domestication process (Tables S6, S7). For example, Glyma.17G128200 and Glyma.10G295400 are associated with soybean seed yield traits [ 27 , 28 ], Glyma.15G130000 is associated with soybean seed protein concentration [ 29 ], Glyma.11G092100 was demonstrated to directly influence the anabolism of sucrose in soybean [ 30 ], and Glyma.12G143200 and Glyma.13G285300 are associated with soybean cyst nematode and root-lesion nematode resistance, respectively [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The leucine-rich repeat (LRR) family protein is well-known for controlling disease resistance in crops, including soybean [ 78 ]. In soybean, LRR has been reported to regulate the immune response to Phytophthora root rot [ 79 ], coordinate the responses against root-lesion nematode [ 80 ], and mediate the response to soybean mosaic virus [ 81 ]. This study also revealed the contribution of the LRR domain in the resistance to red leaf blotch disease in soybean production.…”
Section: Discussionmentioning
confidence: 99%